Prediction of transition to psychosis from an at-risk mental state using structural neuroimaging, genetic, and environmental data - Tavares, Vânia; Vassos, Evangelos; Marquand, Andre; Stone, James; Valli, Isabel; Barker, Gareth J.; Ferreira, Hugo; Prata, Diana (Frontiers in Psychiatry, 2023)
Psychosis is usually preceded by a prodromal phase in which patients are clinically identified as being at in an ‘At Risk Mental State’ (ARMS). A few studies have demonstrated the feasibility of predicting psychosis transition from an ARMS using structural magnetic resonance imaging (sMRI) data and machine learning (ML) methods. However, the reliability of these findings is unclear due to possible sampling bias. Moreover, the value of genetic and environmental data in predicting transition to psychosis from an ARMS is yet to be explored. In this study we aimed to predict transition to psychosis from an ARMS using a combination of ML, sMRI, genome-wide genotypes, and environmental risk factors as predictors, in a sample drawn from a pool of 246 ARMS subjects (60 of whom later transitioned to psychosis). First, the modality-specific values in predicting transition to psychosis were evaluated using several: a) feature types; b) feature manipulation strategies; c) ML algorithms; d) cross-validation strategies, as well as sample balancing and bootstrapping. Subsequently, the modalities whose at least 60% of the classification models showed an balanced accuracy (BAC) statistically better than chance level were included in a multimodal classification model. Results showed that none of the modalities alone, i.e. neuroimaging, genetic or environmental data, could predict psychosis from an ARMS statistically better than chance and, as such, no multimodal classification model was trained/tested. These results suggest that the value of structural MRI data and genome-wide genotypes in predicting psychosis from an ARMS, which has been fostered by previous evidence, should be reconsidered.